The Revolving Door between Large Audit Firms and the PCAOB: Implications for Future Inspection Reports and Audit Quality - Hendricks, Bradley E.; Landsman, Wayne R.; Peña-Romera, F. Dimas (The Accounting Review, 2022)
ABSTRACT This study examines whether audit firms hire former PCAOB employees in response to negative PCAOB inspection reports, and whether such hiring leads to reductions in future inspection deficiencies and an increase in audit quality. We find that the number of PCAOB employees hired by large audit firms is positively related to the number of deficiencies reported in their prior inspection reports, and that the number of deficiencies reported in firms' future inspection reports is negatively associated with the number of former PCAOB employees hired. However, we find no significant association between the number of former PCAOB employees that a firm hires and improvement in audit quality. These findings suggest that former PCAOB personnel possess valuable knowledge about how to perform and document audit procedures to satisfy PCAOB reviewers, but that this expertise does not necessarily have direct implications for the accuracy and reliability of clients' financial reports. JEL Classifications: G28; G38; M41; M49.